2014
DOI: 10.1038/onc.2014.154
|View full text |Cite
|
Sign up to set email alerts
|

Smoking accelerates pancreatic cancer progression by promoting differentiation of MDSCs and inducing HB-EGF expression in macrophages

Abstract: Smoking is an established risk factor for pancreatic cancer (PC), but late diagnosis limits the evaluation of its mechanistic role in the progression of PC. We used a well-established genetically engineered mouse model (LSL-K-rasG12D) of PC to elucidate the role of smoking during initiation and development of pancreatic intraepithelial neoplasia (PanIN). The 10-week-old floxed mice (K-rasG12D; Pdx-1cre) and their control unfloxed (LSL-K-rasG12D) littermates were exposed to cigarette smoke (total suspended part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 52 publications
(65 reference statements)
2
36
0
Order By: Relevance
“…The mechanism of this phenomenon is not yet clear. One possible explanation revealed that cigarette smoking could promote the mobilization and accumulation of (MDSCs) and increase the level of interferon-γ in TME [29]. Meanwhile, other studies demonstrated that MDSCs could induce Foxp3+ Tregs development and expansion via the production of cytokines, such as IFN-γ, or direct cell-cell interactions [3032].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of this phenomenon is not yet clear. One possible explanation revealed that cigarette smoking could promote the mobilization and accumulation of (MDSCs) and increase the level of interferon-γ in TME [29]. Meanwhile, other studies demonstrated that MDSCs could induce Foxp3+ Tregs development and expansion via the production of cytokines, such as IFN-γ, or direct cell-cell interactions [3032].…”
Section: Discussionmentioning
confidence: 99%
“…PC cells were grown on sterilized cover slips for 24 h, serum starved for 8 h and treated with appropriate vehicle control (media, ethanol or DMSO), DCA, CDCA, and inhibitors for indicated time‐points. After the treatment, immunofluorescence staining with specific primary antibodies was performed as described previously (Kumar et al., 2015b). For immunohistofluorescence, we deparaffinized tissue sections with xylene, rehydrated with decreasing concentrations of ethanol and incubated tissues for 30 min with 3% H 2 O 2 : methanol solution.…”
Section: Methodsmentioning
confidence: 99%
“…These studies revealed that that tobacco exerts dramatic effects in the pancreas. Thus, exposure of KC mice to cigarette smoke (for 20 weeks) enhances ADM formation and accelerates PanIN development in conjunction with decreased number of myeloid-derived suppressor cells (MDSCs) and an increase in the number of M2 macrophages and dendritic cells in the pancreas [37], underscoring the deleterious effects of cigarette smoke on the immune system in the pancreatic microenvironment that has already been compromised by the expression of oncogenic Kras .…”
Section: Mechanisms Of Effects Of Tobacco and Alcoholmentioning
confidence: 99%